Identification of Clusterin in Buffalo (Bubalus Bubalis) Semen and its Relation to Semen Quality - Kumari, Manisha; Kumar, Pradeep; Kumar, Dharmendra; Yadav , P S (The Indian Journal of Animal Reproduction, 2024)
The study aimed to identify the clusterin in buffalo seminal plasma and compare the semen quality of high and low clusterin-positive sperm (CPS) bearing buffalo bulls. Semen was collected with artificial vagina technique from buffalo bulls. The anti-clusterin antibody recognized one protein band of 40 kDa in the western blot. Based on the results of the immunofluorescence assay, bulls were divided into two groups: high CPS and low CPS bulls. The expression of clusterin on sperm cells was further reflected in terms of their quality. The high CPS bulls showed significantly (P<0.05) low values for total, progressive, and rapid sperm motility compared to low CPS bulls. The curve linear velocity (VCL), straight linear velocity (VSL), straightness (STR), and linearity (LIN) of sperm were found to be significantly higher in low CPS bulls than in high CPS bulls. Further, high CPS bulls showed significantly more sperm abnormality than that of low CPS bulls. The plasma membrane integrity of sperm was found more in low CPS bulls compared to high CPS bulls. In conclusion, an anti-clusterin antibody recognized 40 kDa clusterin in buffalo seminal plasma. The high percentage of CPCs in buffalo semen is a negative marker for semen quality.